PENGARUH CAMELS TERHADAP RETURN ON ASSET PADA BANK UMUM SWASTA NASIONAL DEVISA PERIODE 2017-2020 - Vivi Alingga Dewi (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This research aims to determine the outcome of capital, asset, management, earnings, liquidity, and sensitivity to market risk on Return on Assets in the foreign exchange national private commercial bank from 2017 to 2020. This study uses a quantitative approach with secondary data types obtained from the bank's annual report. This study uses purposes sampling techniques to get samples. The samples are 23 foreign exchange national private commercial banks. This research uses multiple linear regression analysis with SPSS 24 software. The results show only earnings proxied by BOPO influence Return on assets with adverse decisions because of low-interest income while operating costs are high. Capital does not affect ROA because some of the banking capital is used to overcome the failure of banking operations. The banking sector is not optimal in utilizing capital in services. The asset has no effect because of the high capital value to cover the risk of a non-performing loan. Management does not affect ROA because there is an adjustment process due to the increased interest rates in the previous year. Liquidity does not affect ROA because the lending value doesn't match the loan's quality. Sensitivity to market risk has no influence on Return on Asset because the difference in foreign exchange rates doesn't work correctly. Managers should use the annual report as an evaluation material and a basis for policymaking in the next period and multiply information to form the right strategy in maximizing company value in the eyes of stakeholders through profitability.